Impact of population admixture on the distribution of immune response co-stimulatory genes polymorphisms in a Brazilian population - Cassiano, Gustavo Capatti [UNESP]; Melo Santos, Eduardo Jose; Thomaz Maia, Maria Helena; Furini, Adriana da Cruz; Storti-Melo, Luciane Moreno; Batista Tomaz, Franciele Maira; Alves Trindade, Pamella Cristina; Capobianco, Marcela Petrolini [UNESP]; Trindade Amador, Marcos Antonio; Rachid Viana, Giselle Maria; Povoa, Marinete Marins; Batista Santos, Sidney Emanuel; et al. (Elsevier B.V., 2015)
Co-stimulatory molecules are essential in the orchestration of immune response and polymorphisms in their genes are associated with various diseases. However, in the case of variable allele frequencies among continental populations, this variation can lead to biases in genetic studies conducted in admixed populations such as those from Brazil. The aim of this study was to evaluate the influence of genomic ancestry on distributions of co-stimulatory genes polymorphisms in an admixed Brazilian population. A total of 273 individuals from the north of Brazil participated in this study. Nine single nucleotide polymorphisms in 7 genes (CD28, CTLA4, ICOS, CD86, CD40, CD40L and BLYS) were determined by polymerase chain reaction-restriction fragment length polymorphism. We also investigated 48 insertion/deletion ancestry markers to characterize individual African, European and Amerindian ancestry proportions in the samples. The analysis showed that the main contribution was European (43.9%) but also a significant contribution of African (31.6%) and Amerindian (24.5%) ancestry. ICOS, CD40L and CD86 polymorphisms were associated with genomic ancestry. However there were no significant differences in the proportions of ancestry for the other SNPs and haplotypes studied. Our findings reinforce the need to apply AIMs in genetic association studies involving these polymorphisms in the Brazilian population. (c) 2015 American Society for Histocompatibility and Immunogenetics. Published by Elsevier Inc. All rights reserved.
Keywords: Admixture population; Ancestry markers; Immunogenetics